The Effect Of Calf Raise Exercise And Core Stability Exercise On Balance In The Elderly Puskesmas Tanjung Morawa - Raynald Ignasius Ginting; Aktifiti Gulo (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Balance disorders are a common issue among the elderly, increasing the risk of falls. Therefore, it is important to conduct studies on balance exercises to reduce this risk. This research focuses on two types of balance exercises: calf raise exercise and core stability exercise. The aim of this study is to analyze the effects of these two exercises on improving balance in the elderly. This study uses a quasi-experimental design with a pre-post test approach, dividing the sample into two groups. The sampling technique used is purposive sampling, involving 15 participants who meet the inclusion criteria. The measurement tool used is the Timed Up and Go Test (TUGT). To analyze the differences in effects between calf raise exercise and core stability exercise, the Shapiro-Wilk Test, Paired Sample T-Test, and Independent T-Test were applied. The results showed that both types of exercises led to improvements in balance, with calf raise exercise (p=0.001) and core stability exercise (p=0.000). The Independent T-Test results showed a p-value of 0.036, indicating a significant difference between the two exercises, with core stability exercise being more effective in improving balance in the elderly.